From complexity to life : on the emergence of life and meaning - Gregersen, Niels Henrik, 1956- (OUP E-Books., 2003)
Brings together a group of scholars in the sciences of complexity, and workers on the interface of science and religion, to explore the implications of complexity studies. This book includes an introduction to complexity studies and explores the concept of information in physics and biology and various philosophical and religious perspectives.